Localisation of iron in wheat grain using high resolution secondary ion mass spectrometry - Moore, K; Grovenor, C; Zhao, F; Gritsch, C; Tosi, P; Hawkesford, M; McGrath, S; Shewry, P (2012)
Insufficient iron (Fe) is one of the most prevalent micronutrient deficiencies in humans, with billions of people affected. Cereal grains are an important source of Fe for humans but the bioavailability of Fe in cereals is generally low. Information regarding the cellular and sub-cellular localisation of Fe in wheat grain will aid optimising nutrient delivery for human health. In this study high resolution secondary ion mass spectrometry (NanoSIMS) was used to map the distribution of Fe in the aleurone layer and in the endosperm of immature wheat grain. Iron was shown to be localised strongly in the phytin globoids in the aleurone cells and to a lesser extent in the cytoplasm around the starch granules in the endosperm. © 2011 Elsevier Ltd.